Analysis of Health Belief Model regarding Human Papillomavirus Vaccination among Female Employees at Sukabumi Regency Government - Aninda Nurul Lita; Chahya Kharin Herbawani (EMBRIO: Jurnal Kebidanan, 2022)
The high rate of cervical cancer case confirms it as the second most common cancer in Indonesia which required specific management and primary prevention efforts for everyone. The appeal issued by the Ministry of Health regarding HPV vaccination which will be mandatory as an effort to reduce cervical cancer rates in Indonesia. This study aims to analyze the health belief model as the influential factor for the willingness to get HPV vaccination as an effort to prevent cervical cancer among female employees in Sukabumi Regency government in 2022. This was a quantitative study with cross-sectional design. Data were collected among 213 respondents who were selected using purposive sampling technique. The results showed that 50.7% of respondents were willing to get HPV vaccination. Meanwhile, 49,3% of respondents were not willing to get HPV vaccination. There was a relationship between perceived susceptibility, benefit, obstacle, cues to action, and self-efficacy with the willingness to get HPV vaccination. Meanwhile, the perceived severity was not related to the willingness to get HPV vaccination. In the multivariate analysis, it was found that cues to action (POR=5,477; 95% CI=2,6-11,2) had the most significant effect on willingness to get HPV vaccination. It is expected that the current study can be used as an input for the government of Sukabumi Regency to plan for health promotion programs for every agency regarding cervical cancer, especially HPV vaccination.